Implementasi Program TB di Puskesmas Wilayah Kabupaten Magelang - Ita Puji Lestari; Fitria Wulandari (Pro Health Jurnal Ilmiah Kesehatan, 2019)
The prevalence of TB in Central Java in 2012 was 106.42 per 100,000 people. The cases and Case Detection Rate below the standard of 70% are found in the level of cities, regencies or health centers. The lowest CDR is in Magelang regency which is 21.82%. In 2013, it is estimated that there were new cases of lung TB in Magelang regency and there were 1,285 people suffering from positive BTA in 2013 reached 17.89%. This research aims to know the implementation in the program of controlling TB in Public Health Centers in Magelang regency.This research was observational analytic using Cross Sectional Approach. The population is nurse as the program coordinator, as many as 29 people. Data analysis was done by using univariat. The results showed that the description of the implementation of the TB control program in the Magelang District Health Center from the aspects of preparation included in the good category at 62.06% and enough at 37.94%, in the aspect of coverage of activities and controls that were in the good category at 24.14%, enough 68.97% and less at 6.89%, and aspects of recording and reporting included in the good category at 48.27%, just 57.93% and less at 13.79%. Public Health Centers have to compile the instruments to measure the effectiveness of the coordination in the program, and to make the activities of education and cadre training of TB disease periodically. Â Public Health Center should make cooperative networks with stakeholders and society, should compile the development of reward system for the employees and TB cadres who have contribution and active roles, and should compile a specific task force for the program of controlling TB which are legalized with the decree letter from the Public Health Center.